METODE SOSIODRAMA DALAM PENDIDIKAN AGAMA ISLAM - Rahendra Maya (Sekolah Tinggi Agama Islam Al Hidayah, 2015)
Learning-teaching process or teaching-learning process need learning methodology. It used to achieve goal of learning-teaching or teaching-learning as planning and target. There are two model of method. The first, method is tehcnique or way. It's mean way to send the content of message to audiens. The second, in learning methodology, method are term of model, strategy, learning technique and learning tactics.Â Keyword: metode sosiodrama, metodologi pembelajaran, hukum sosiodrama dalam Islam